2015
DOI: 10.1016/j.indcrop.2015.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Gamma irradiation improves the extractability of phenolic compounds in Ginkgo biloba L.

Abstract: Irradiation has been increasingly recognized as an effective decontamination technique that ensures the chemical and organoleptic quality of medicinal and aromatic plants.The aim of the present study was to evaluate the effects of gamma irradiation in the phenolic compounds of Ginkgo biloba L. (infusion and methanol/water extract), widely used in traditional medicine and in dietary supplements. Twenty-five compounds were detected, eighteen of which were flavonoids, one phenolic acid, five terpene lactones and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…Small but significant increases were observed in the levels of methyleriodictyol-O-pentosylhexoside, luteolin-7-O-glucoside and eriodictyol, and consequently in total flavonoid content. This is in agreement with Pereira et al, (2015c) and Alothman, Bhat, & Karim, (2009) who also observed that irradiation at 10 kGy dose caused an increase in some individual phenolic compounds in the infusions of Ginkgo biloba. These results could be explained by an increase in compounds extractability due to depolymerization and release from cell wall polysaccharides produced by the irradiation process, as stated above.…”
Section: Pulegioides T Praecox T Serpyllum)supporting
confidence: 92%
“…Small but significant increases were observed in the levels of methyleriodictyol-O-pentosylhexoside, luteolin-7-O-glucoside and eriodictyol, and consequently in total flavonoid content. This is in agreement with Pereira et al, (2015c) and Alothman, Bhat, & Karim, (2009) who also observed that irradiation at 10 kGy dose caused an increase in some individual phenolic compounds in the infusions of Ginkgo biloba. These results could be explained by an increase in compounds extractability due to depolymerization and release from cell wall polysaccharides produced by the irradiation process, as stated above.…”
Section: Pulegioides T Praecox T Serpyllum)supporting
confidence: 92%
“…In turn, a small but statistically signifi cant increase was reported in luteolin and eriodictyol contents of the ethanolic extracts of the irradiated and non-irradiated wild thyme (Table 1). Higher contents of total and some individual fl avonoids in both extracts and infusions of irradiated dry plants compared to the nonirradiated controls were described in literature [de Camargo et al, 2012;Pereira et al, 2015;2016a]. This phenomenon was explained by enhancement of compounds extractability caused by the γ-irradiation process.…”
Section: Resultsmentioning
confidence: 78%
“…Their content in the ethanolic extracts was in a decreasing order of: rosmarinic acid >> chlorogenic acid > caffeic acid > p-coumaric acid (Table 1) Flavonoids belonging to subclasses of fl avones and fl avanones were found in the analyzed wild thyme ethanolic extracts. Luteolin-7-O-glucoside (13), luteolin (26) and apigenin (28) were recognized as compounds form the fi rst subclass ( Figure 2, Table 1). Based on UV-DAD spectra (data not shown), also some non-identifi ed compounds (5,7,11,14,16,19) could be included to fl avones.…”
Section: Resultsmentioning
confidence: 99%
“…The leaf extracts of various tree species (Frédérich et al, 2009;Katsube et al, 2009;Germanò et al, 2012;Reinoso et al, 2012;Santos et al, 2013;Liu et al, 2015;Pereira et al, 2015;Talhaoui et al, 2015) have been known to exhibit several benefical effects (antioxidant, anticancer, anti-inflammatory, antidiabetic, etc. ) on human health on consumption.…”
Section: Introductionmentioning
confidence: 99%